Pengaruh kebiasaan membaca melalui perpustakaan digital bukuaku terhadap kemampuan membaca pemahaman peserta didik kelas v sd se-gugus III kecamatan banjarsari - Alawiyah, Nur Azizah; Karsono, Karsono (Didaktika Dwija Indria, 2026)
This study aims to examine the use of the BukuAku digital library in supporting reading comprehension among fifth-grade elemntary student in Gugus III, Banjarsari District. While digital libraries have potenstial to increase access to reading materials, their effectiveness in enhacing student’s reading comprehension remains uncertain. This research apllies a quantitative approach with a quasi-experimental design involving one experimental class using BukuAku and one control class using the Let’s Read application. Data were collected through pre-test, post-test, and reading habit questionnaires an analyzed using the Mann-Whitney test, Wilcoxon signed-rank test, and effect size. The result show that although experimental group’s post-test score improved, the increase was not statistically significant. However, the experimental group demonstrated significantly higher reading habit scores than the control group. These findings indicate that digital libraries like BukuAku have potential but require structured instructional strategies and teacher support to effectively enhace reading comprehension in elementary school.